Alcohol disinhibition of behaviors in C. elegans. - Stephen M Topper; Sara C Aguilar; Viktoria Y Topper; Erin Elbel; Jonathan T Pierce-Shimomura (PLoS ONE)
Alcohol has a wide variety of effects on physiology and behavior. One of the most well-recognized behavioral effects is disinhibition, where behaviors that are normally suppressed are displayed following intoxication. A large body of evidence has shown that alcohol-induced disinhibition in humans affects attention, verbal, sexual, and locomotor behaviors. Similar behavioral disinhibition is also seen in many animal models of ethanol response, from invertebrates to mammals and primates. Here we describe several examples of disinhibition in the nematode C. elegans. The nematode displays distinct behavioral states associated with locomotion (crawling on land and swimming in water) that are mediated by dopamine. On land, animals crawl and feed freely, but these behaviors are inhibited in water. We found that additional behaviors, including a variety of escape responses are also inhibited in water. Whereas alcohol non-specifically impaired locomotion, feeding, and escape responses in worms on land, alcohol specifically disinhibited these behaviors in worms immersed in water. Loss of dopamine signaling relieved disinhibition of feeding behavior, while loss of the D1-like dopamine receptor DOP-4 impaired the ethanol-induced disinhibition of crawling. The powerful genetics and simple nervous system of C. elegans may help uncover conserved molecular mechanisms that underlie alcohol-induced disinhibition of behaviors in higher animals.